Public sector information technology initiatives: implications for programs of public administration - Brown, Mary Maureen; Brudney, Jeffrey L. (1998)
On the 10th anniversary of the recommendations published by the National Association of Schools of Public Affairs and Administration (NASPAA) on information system instruction in schools and departments of public administration, sweeping information management reforms were instituted throughout the federal sector by the passage of the Clinger-Cohen Act (CCA) of 1996. This research examines the extent to which these programs prepare students for the issues they will face in managing information resources in government. Based on a survey of 106 schools and departments of public administration, few programs are covering the topics recently mandated by the CCA or recommended a decade ago by NASPAA. If governments are to achieve the benefits of contemporary technological advances, schools and departments of public administration must reexamine their current approach to instruction in information resource management. - Reproduced
Keywords: Public administration